Sistem Pakar Diagnosa Penyakit Pada Sugar Glider Dengan Metode Forward Chaining Berbasis Web - Alvenio Farhan Prayogo; Fatkhul Amin (JURNAL MAHAJANA INFORMASI, 2021)
Sugar Glider, Forward Chaining, Disease, Expert System An expert system is a computer-based application that uses knowledge, facts, and reasoning techniques to solve problems as thought by experts. Expert systems provide added value to technology to help solve problems in the health sector (Kusrini, 2006). Sugar Glider (Petaurus Breviceps) is a marsupial mammal that is active at night (nocturnal). Keeping a Sugar Glider must require good and correct care to avoid all diseases. Based on these problems, this study aims to build an expert system that is able to combine the knowledge of an expert with artificial intelligence technology to diagnose disease in Sugar Glider. By referring to the formulation of the problem, this study aims to build an expert system design to diagnose diseases in Sugar Glider that are maintained by adopters or caretakers. Research conducted by researchers is related to the Forward Chaining method as well as information about diseases in Sugar Glider. The method used in the development of this system is the Linear Sequential Model or commonly called the waterfall model. The data used in this study were obtained from several collected references. From these data in this study resulted in an accuracy of 87.5% by testing 8 times of the application made. An expert system for diagnosing diseases in sugar gliders can make it easier for users to diagnose diseases.